Activation of the CaMKII-Sarm1-ASK1-p38 MAP kinase pathway protects against axon degeneration caused by loss of mitochondria - Chen Ding; Youjun Wu; Hadas Dabas; Marc Hammarlund (eLife, 2022)
Mitochondrial defects are tightly linked to axon degeneration, yet the underlying cellular mechanisms remain poorly understood. In Caenorhabditis elegans, PVQ axons that lack mitochondria degenerate spontaneously with age. Using an unbiased genetic screen, we found that cell-specific activation of CaMKII/UNC-43 suppresses axon degeneration due to loss of mitochondria. Unexpectedly, CaMKII/UNC-43 activates the conserved Sarm1/TIR-1-ASK1/NSY-1-p38 MAPK pathway and eventually the transcription factor CEBP-1 to protect against degeneration. In addition, we show that disrupting a trafficking complex composed of calsyntenin/CASY-1, Mint/LIN-10, and kinesin suppresses axon degeneration. Further analysis indicates that disruption of this trafficking complex activates the CaMKII-Sarm1-MAPK pathway through L-type voltage-gated calcium channels. Our findings identify CaMKII as a pivot point between mitochondrial defects and axon degeneration, describe how it is regulated, and uncover a surprising neuroprotective role for the Sarm1-p38 MAPK pathway in this context.